2007
DOI: 10.1002/pds.1355
|View full text |Cite
|
Sign up to set email alerts
|

Trends in antidepressant overdoses

Abstract: The dramatic rise in United States antidepressant overdoses has not been reflected in antidepressant overdose fatalities nor in hospitalizations. If the marked increase in antidepressant overdoses in the United States had involved TCAs rather than SSRIs, then there would have been roughly 300 excess deaths annually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 65 publications
0
29
0
1
Order By: Relevance
“…million prescriptions were about 10 times higher for TCAs than for SSRIs (Morgan et al, 2004). A similar picture has emerged in the US, where it is has been estimated that if the marked increase in antidepressant overdoses 1983-2003 had involved TCAs rather than SSRIs, then there would have been some 300 excess deaths annually (McKenzie and McFarland, 2007).…”
Section: Tricyclic Antidepressantsmentioning
confidence: 87%
“…million prescriptions were about 10 times higher for TCAs than for SSRIs (Morgan et al, 2004). A similar picture has emerged in the US, where it is has been estimated that if the marked increase in antidepressant overdoses 1983-2003 had involved TCAs rather than SSRIs, then there would have been some 300 excess deaths annually (McKenzie and McFarland, 2007).…”
Section: Tricyclic Antidepressantsmentioning
confidence: 87%
“…39 Although there is insufficient evidence to support a particular therapy in CA overdose, the use of sodium bicarbonate to alkalinize blood to a pH of 7.45 to 7.55 is still considered the primary therapy to prevent and treat cardiac arrhythmias associated with CAs. 40 Proposed criteria for initiating sodium bicarbonate have been variable (Table 4), but in general we recommend blood alkalinization with QRS Ͼ 120 ms. Hypertonic saline solution may be a therapeutic option in refractory cases based on animal studies and limited clinical experience.…”
Section: Antidepressantsmentioning
confidence: 99%
“…This is unlikely due to suicide attempts after initiating antidepressants, which has primarily been a concern for children and adolescents, 14 or to poisoning by these drugs, as it is relatively rare. 15 Several studies have reported no benefit for short-term antidepressant therapy in the treatment of depression, but less is known about the effects on pain. 16,17 Short-term antidepressant therapy may be an indicator for non-adherence 16 to this medication and increased reliance on riskier medications for pain management.…”
Section: Discussionmentioning
confidence: 99%